(untitled) (Journal of Fatima Jinnah Medical University, 2018)
The incidence of vascular injuries of extremities is scaling new heights in Pakistan. This substantial vascular surgical profile of general surgery demands significant knowledge and skill to manage traumatic vascular injuries. Aims & Objectives: • To record the mode of presentation of acute peripheral vascular injuries in limb trauma patients admitted through Accident and Emergency Department, Jinnah Hospital, Lahore. • To evaluate and analyze the outcome of various types of vascular repair carried out for such injuries. • Comparison of results with international data. Study Design: Prospective analytical and observational study. Setting: Conducted in Surgical Unit-I, Jinnah Hospital, Lahore Period: From January 2015 to January 2016. Methodology: A total of 31 limb trauma patients with associated acute vascular injuries were managed. Results: 30 patients were male and one was female with mean age of 27 years. Major limb trauma associated with vascular injuries were caused by firearm in 19 (61.2%) cases, stab in 3 (9.6%) and blunt trauma in 9(29%).Arterial bleeding from the wound was the commonest presentation in 15 (48.3%) then deficient distal pulses in 13 (41.9%). Upper limb was involved in 15(48.3%) cases and lower limb in 16 (51.6%)cases. 27 (87%) patients had arterialinjuries,4(12.9%) isolated venous and 8 (25.8%) had associated venous lesions. Axillary artery was the most common vessel injured in 7 (22.5%) cases. Autogenous saphenous vein graft was interposed in 17 (62.9%)patients, 6 (22.2%) had endtoend repair and 4 (14.81%) had lateral repair of injured artery. Lateral venorrhaphy was done in 7 (22.58%) venous injuries. 6 (19.3%) developed postoperative wound infection, 6(30%) out of 20fasciotomy wound infection and 5 (16.1%) got distal limb edema. Amputation and mortality rates were 3.22% each. Conclusion: Timely surgical intervention, regular use of interposition vein graft and low threshold for fasciotomy gave better results. Time is the decisive feature for final outcome of vascular surgery.